Expanding the application of tyrosine: engineering microbes for the production of tyrosine and its derivatives - Shen, Jian; Liu, Pengfu; Zhang, Bin; Ye, Bangce; Xu, Shunqing; Su, Weike; Chu, Xiaohe (Frontiers in Bioengineering and Biotechnology, 2025)
Aromatic compounds are widely used in the fields of medicine, chemical industry, and food, with a considerable market size. Tyrosine, an aromatic amino acid, boasts not only a wide range of applications but also serves as a valuable precursor for synthesizing a diverse array of high-value aromatic compounds. Amid growing concerns over environmental and resource challenges, the adoption of green, clean, and sustainable biotechnology for producing aromatic compounds is gaining increasing recognition as a viable alternative to traditional chemical synthesis and plant extraction methods. This article provides an overview of the current status of tyrosine biomanufacturing and explores the methods for generating derivatives, including resveratrol, levodopa, p-coumaric acid, caffeic acid, zosteric acid, tyrosol, hydroxytyrosol, tanshinol, naringenin, eriodictyol, and salidroside, using tyrosine as a primary raw material. Furthermore, this review examines the current challenges and outlines future directions for microbial fermentation for the production of tyrosine and its derivatives.